The effects of breeder age and laying period on hatchability and some external egg quality characteristics in breeder geese* - Eroglu, Mehmet; Erisir, Zeki (Institute of Genetics and Animal Biotechnology of the Polish Academy of Sciences, 2022)
This study was carried out to determine the effects of breeder age, laying period on hatchability and some external egg characteristics in geese. 3240 eggs from one, two, three-year-old breeder flocks of geese were examined in two different periods (the second part of March + the first part of April and the second part of May + the first part of June). In the first period fertility rates were 84.63, 87.40, and 88.33%; hatching from set eggs were 62.40, 68.51, and 70.00%; hatching from fertilized eggs were 73.74, 78.37, and 79.28% in one, two, three-year-old breeder flocks of geese, respectively. In the second laying period, fertility rates were 82.40, 84.44, and 85.00%; hatching from set eggs were 69.63, 67.77, and 65.92%; hatching from fertile eggs were 84.62, 80.34, and 77.54% in one, two, three-year-old breeder flocks of geese, respectively. In terms of the laying period, the fertility rates were 86.79 and 83.95%, hatching from set eggs were 66.97 and 67.77%; hatching from fertilized eggs were77.13 and 80.83%; the embryonic mortality rates were 16.04 and 12.16%, respectively. The differences in egg weight (P <0.001) and shape index (P <0.01) between geese in different breeder ages were found to be statistically significant. The highest egg weight was 176.41 g in 3-year-old breeder geese, while the highest shape index was seen in the 1-year-old breeder geese with 65.78%. According to these findings, whereas laying period only affects shape index, breeder age affects both egg weight and shape index. In addition, hatchability characteristics were relatively higher in two, three-year-old breeders than one-year-old and the first period of the laying season. © 2022, Institute of Genetics and Animal Biotechnology of the Polish Academy of Sciences. All rights reserved.
Keywords: breeder age; egg quality; fertility; goose; hatchability; laying season